SISTEM PENDUKUNG KEPUTUSAN REKRUTMEN ANGGOTA BARU BAWASLU PROVINSI JAMBI: Decision Support System;PhpMyAdmin;Visual Basic. - Afrizal , Afrizal; Piska, Yeni (JURNAL AKADEMIKA, 2021)
Recruitment is very important for offices to get new recruits to occupy a position. In some offices, the process of admitting new members is still not done professionally. This occurs because there is no systematic standard method for assessing the eligibility of new recruits. The decision support system application for recruiting new members was built using the Simple Additive Weighting (SAW) method. with several criteria, namely: knowledge, interviews, written tests, administration. This method was chosen because it can determine the weight value for each attribute, then followed by a ranking process that will select the best alternative from a number of alternatives, in this case the alternative is those that are entitled to be accepted as new members based on the specified criteria. Based on the test results, this decision support system uses php myAdmin and visual basic 6.0 to design the program. The system built can simplify and accelerate the process of selecting new recruits and help managers of the Human Resources (HR) division.